2022
DOI: 10.1021/acs.accounts.1c00675
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in Organic Semiconductors: The Perspective from Nonadiabatic Molecular Dynamics

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Organic semiconductors (OSs) are an exciting class of materials that have enabled disruptive technologies in this century including large-area electronics, flexible displays, and inexpensive solar cells. All of these technologies rely on the motion of electrical charges within the material and the diffusivity of these charges critically determines their performance. In this respect, it is remarkable that the nature of the charge transport in these materials has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 78 publications
(201 reference statements)
3
58
0
Order By: Relevance
“…The choice of the electronic basis functions, {Φ i }, deserves a separate discussion. In many prior works on NA-MD simulations, such functions are chosen as either KS or MO orbitals, ,,, or as the Slater determinants (SDs). , ,, Although the adoption of the SD basis has been helpful in enabling modeling coupled electron–nuclear dynamics, for example, in Auger processes, such functions still miss an important physical constraint of being the eigenfunctions of the spin operator Ŝ 2 . A proper solution is the use of the spin-adapted configurations (SACs).…”
Section: Theory and Methodsmentioning
confidence: 99%
“…The choice of the electronic basis functions, {Φ i }, deserves a separate discussion. In many prior works on NA-MD simulations, such functions are chosen as either KS or MO orbitals, ,,, or as the Slater determinants (SDs). , ,, Although the adoption of the SD basis has been helpful in enabling modeling coupled electron–nuclear dynamics, for example, in Auger processes, such functions still miss an important physical constraint of being the eigenfunctions of the spin operator Ŝ 2 . A proper solution is the use of the spin-adapted configurations (SACs).…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Incredible efforts have been made in recent decades to elucidate the molecular underpinnings of such phenomena using both experimental and theoretical techniques. For example, two-dimensional electronic spectroscopy provides rich knowledge on ultrafast dynamical information of CT and EET in realistic light-harvesting molecules in complex or condensed-phase systems. Theoretical description of nonadiabatic dynamics has advanced significantly. Mixed quantum–classical dynamics such as mean-field Ehrenfest , and fewest-switches surface hopping (FSSH) , are the most popular approaches for simulating the nonadiabatic dynamics in molecular or extended nanoscale systems (up to hundreds of atoms) with the help of on-the-fly electronic structure calculations and the recent machine-learning-based acceleration. …”
Section: Introductionmentioning
confidence: 99%
“…In this respect, we note that previous nonadiabatic molecular dynamics simulations showed that polarons in crystalline pentacene are delocalized over 18 molecules on average at room temperature. 53 At 0 K, corresponding to the present CDFT optimizations, the charge will occupy the fully delocalized state at the top of the valence band. The physical reason for the nonexistence of fully localized polaronic states is that reorganization energy is not sufficiently large in these materials compared to electronic couplings to support fully localized states, in stark contrast to, e.g., the F centers in the MgO system ( Section 3.1.2 ) and the Ru 2+ –Ru 3+ self-exchange reaction ( Section 3.2.3 ).…”
Section: Resultsmentioning
confidence: 94%